Research Trends on the Integration of Digitalization in Mathematics Education to Develop Students’ Affective Domain: A Systematic Literature Review - Puput Yolanda; Rhomiy Handican; Dian Maisaroh (Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to map research trends and directions related to the integration of digitalization in mathematics education for the development of students’ affective domains through a Systematic Literature Review (SLR). A total of 175 articles published in SINTA 2–accredited mathematics education journals over the past three years were analyzed. The identification, screening, and reporting processes followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The analysis focused on five main aspects: research methods, types of affective domains investigated, research participants, and forms of digital learning used. The results indicate that quantitative and research-and-development (R&D) approaches dominate the literature, with learning motivation, attitudes toward mathematics, and learning interest as the most frequently examined affective aspects. Junior secondary school students (SMP/MTs) were the most common research participants, while studies involving mathematics teachers remain limited. In terms of digital media, e-modules and Android-based applications were the most frequently utilized. These findings suggest that current research on the digitalization of mathematics education primarily focuses on affective aspects that are relatively easy to measure. This study provides a systematic overview of recent research trends and highlights future research opportunities, particularly in exploring more complex affective dimensions and innovative digital technologies.